Risk factors associated with cutaneous anthrax outbreaks in humans in Bangladesh - Chowdhury, Sukanta; Islam, Md. Saiful; Haider, Najmul; Hossain, Muhammad Belal; Alam, Md. Ashraful; Sharif, Md. Ahmad Raihan; Uzzaman, M. Salim; Rahman, Mahbubur; Rahman, Mahmudur; Haque, Farhana (Frontiers in Public Health, 2024)
Objectives: To determine the risk factors associated with cutaneous anthrax infection in humans.Methods: During 2013-2016, we investigated total 26 anthrax outbreaks across the country. We additionally conducted a case-control study to identify risk factors by recruiting four controls for each enrolled case. Adjusted odds ratios (aOR) and 95% confidence intervals (CI) were estimated to identify risk factors using multivariate logistic regression.Results: Of the 4,216 individuals exposed to sick and slaughtered livestock, a total of 1,210 suspected cutaneous cases were identified. The attack rate of suspected cutaneous cases was 20%.Persons who had a cut injury (aOR 19.0, CI: 4.1-88.9), weighed raw meat (aOR 5.7, CI: 3.0-10.8), mixed bones and meat (aOR 4.6, CI: 3.0-7.1), observed livestock slaughtering (aOR 2.7, CI: 2.0-4.0), had direct contact to an anthrax suspected live livestock (aOR 2.7, CI:1.6-4.5), slaughtered livestock (aOR 2.3, CI: 1.3-4.0), and who did not wash hands with soap and water after direct contact (aOR 3.2, CI: 2.5-4.1) were more likely to develop cutaneous anthrax than people who did not have these exposures.Having a prior cut injury in the exposed body areas while handling meat and other exposures while slaughtering or butchering sick livestock were identified as potential risk factors for cutaneous anthrax, underscoring the need to prevent slaughtering of sick livestock. However, stopping slaughtering sick livestock, handling meat and livestock by-products to reduce anthrax exposures from livestock to humans may be difficult to achieve given the associated financial incentives in Bangladesh. Interventions such as hand washing with soap during slaughtering and processing meat can be targeted to affected communities to ameliorate some risk.